PENGGUNAAN APOSISI DALAM KITAB YESAYA (SUATU ANALISIS SINTAKSIS) - MAMUKO, IFANA DEBORA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  This study is entitled â€œThe Use of Apposition in The Book of Isaiah (A Syntactic Analysis)â€. The aims of this study is an attempt to identify, classify and analyze the function of apposition found in the book of Isaiah. The data were taken from the book of Isaiah based on the Holy Bible New International Version.Â Â Â Â Â Â Â Â Â Â Â  The method used in this study is descriptive method. There are three steps to finish this study, those are preparation, the writer reads some concepts related to the title about apposition and also browse resources from internet to find journal and skripsi. The second step is data collection. In collecting the data the writer read the book of Isaiah in order to identify and underline the use of apposition. After identifying the writer classifies the apposition based on the concept of Quirk et al. The third step is data analysis. The data were analyzed in term of the function using Aarts and Aarts theory.Â Â Â Â Â Â Â Â Â Â Â  The results of this study shows that there are fifty four appositions found in the book of Isaiah. Concerning types of apposition, they are : 1)Full, Strict and Non-restrictive Apposition; 2)Full, Strict and Restrictive Apposition; 3)Full, Weak and Restrictive Apposition; 4)Partial, Strict and Non-restrictive Appostion; 5)Partial, Weak and Non-restrictive apposition; 6)Partial, Strict and Restrictive Apposition; 7)Partial, Weak and Restrictive Apposition. Regarding the function of apposition found in the book of Isaiah, they are: 1)Subject; 2)Direct Object; 3)Subject Attribute; 4)Object Attribute and 5)Adverbial.Â Key Words: Syntax, Apposition. The Book of Isaiah.